2014
DOI: 10.1371/journal.pone.0089253
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association Analysis of ATP Binding Cassette Protein Family Reveals a Novel Association of ABCB1 Genetic Variants with Epilepsy Risk, but Not with Drug-Resistance

Abstract: Epilepsy constitutes a heterogeneous group of disorders that is characterized by recurrent unprovoked seizures due to widely different etiologies. Multidrug resistance remains a major issue in clinical epileptology, where one third of patients with epilepsy continue to have seizures. Role of efflux transporters in multidrug resistant epilepsy has been attributed to drug-resistant epilepsy although, with discrepant observation in genetic studies. These discrepancies could be attributed to variety of factors suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…Previously, the impact of variants on a drug efflux transporter protein involved in the efflux of antiepileptic drugs, namely P-glycoprotein (Pgp; encoded by ABCB1 or MDR1), has been studied in different ethnic groups [ 46 , 47 ]. However, conflicting results have been reported, with some works indicating an impact on antiepileptic drug resistance [ 48 51 ], while others are in agreement with our observation, showing no effect of ABCB1 3435C>T on CBZ pharmacokinetic and drug response [ 52 55 ].…”
Section: Discussionsupporting
confidence: 89%
“…Previously, the impact of variants on a drug efflux transporter protein involved in the efflux of antiepileptic drugs, namely P-glycoprotein (Pgp; encoded by ABCB1 or MDR1), has been studied in different ethnic groups [ 46 , 47 ]. However, conflicting results have been reported, with some works indicating an impact on antiepileptic drug resistance [ 48 51 ], while others are in agreement with our observation, showing no effect of ABCB1 3435C>T on CBZ pharmacokinetic and drug response [ 52 55 ].…”
Section: Discussionsupporting
confidence: 89%
“…This limitation has been especially true for studies related to AED response in epilepsy. For instance, SNP rs1045642 (c.3435T>C), within ABCB1 , was initially associated with refractory epilepsy, but several other studies could not replicate the results [16, 17]. Indeed, our study showed that SNP rs1045642 presented low importance (MDA = 5.2), to the prediction model proposed (S5 Table).…”
Section: Discussionmentioning
confidence: 50%
“…However, subsequent studies did not replicate these findings [16, 17]. Similarly, SNPs in CYP2C9 (rs1799853 and rs1057910) have been associated with PHT dose requirement [18, 19], and SNPs in CYP2C19 (rs12248560) and CYP2D6 have been considered pharmacogenomic biomarkers for neurologic and psychiatric therapeutic drugs, including clobazam (CLB) and diazepam, receiving approval for use by the U.S. Food and Drug Administration (FDA) [19].…”
Section: Introductionmentioning
confidence: 99%
“…All of them were residents of Kerala, south India, for more than three generations, of which 259 were RE (AED resistant), 201 were AED responsive, and the remaining 275 were non-epilepsy control subjects. Interestingly, this study concluded that variants in the ABCB1 and ABCG2 do not confer a significant risk to AED-resistance in the south Indian population of Kerala, but instead demonstrate an increased vulnerability to epilepsy and associated phenotypes [63].…”
Section: Abc-t Genetic Polymorphisms Refractory Epilepsy and Epileptmentioning
confidence: 80%